Studi Visual Escapism Pada Mahasiswa Sebagai Inspirasi Perancangan Artwear - Napitupulu, Marisi; Soemardi, Ardita Ayulestari; Shinta, Fairus (Practice of Fashion and Textile Education Journal, 2024)
Escapism is the tendency to seek distraction or freedom from unpleasant reality through entertainment or other fantasies. Many people experience escapism, including students also do escapism activities when they feel bored. In this regard, a fashion design is needed as a visual form of escapism among students. The purpose of this fashion design is to describe the visual escapism of college students in a positive direction through fashion design and produce a fashion design in the form of artwear as an effort to direct student escapism in a positive direction. The method used is a qualitative method in the form of literature studies, interviews, and questionnaires. The design method used in this research is as follows: (1) escapism research as research material; (2) visual research in the form of artwear; (3) Moodboard and Colour Scheme; (4) Motif Sketches that symbolise escapism for students; (5) exploration, laser cut, layering, heating and foil painting techniques; (6) production stage; and (7) the final design result in the form of artwear clothing that symbolises visual art escapism for students. Based on this, the design results are obtained in the form of post-production which produces 2 (two) artwear designs using pvc, foil, crinoline, tulle, spandex materials and using heating, foil painting and layering techniques which produce 2 (two) artwear designs in the form of creative videos and catalogues through social media.